Implementation of Differentiated Learning based on Local Wisdom in ELT - Aditama, Madya Giri (ELLITE, 2023)
An educational process must be able to analyze and meet the learning needs of each student. Differentiated learning is an educator's effort to adjust learning activities in the classroom to fulfill the learning needs of students related to readiness to receive new material, students' interests and learning profiles or learning styles of diverse students. Differentiated learning can be done by 1) content differentiation; 2) process differentiation; and 3) product differentiation; The integration of local wisdom in learning gives a real picture to students so students can understand material concepts more easily. This research is qualitative research using a phenomenology approach with data collection methods using observation, interviews and questionnaires where the data subjects were 20 high school and vocational high school English teachers in Batang Regency who applied differentiation learning. According to the results of the research conducted, it was found that 12 teachers applied content differentiation, 14 applied process differentiation, 15 applied product differentiation, and among these results some teachers applied a combination of differentiation in their learning.